2006
DOI: 10.1073/pnas.0510441103
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and genomic deletion status of ataxia telangiectasia mutated ( ATM ) and p53 confer specific gene expression profiles in mantle cell lymphoma

Abstract: Although mantle cell lymphoma (MCL) frequently harbors inactivated ataxia telangiectasia mutated (ATM) and p53 alleles, little is known about the molecular phenotypes caused by these genetic changes. We identified point mutations and genomic deletions in these genes in a series of cyclin D1-positive MCL cases and correlated genotype with gene expression profiles and overall survival. Mutated and͞or deleted ATM and p53 alleles were found in 56% (40͞72) and 26% (21͞82) of the cases examined, respectively. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
103
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 34 publications
14
103
1
Order By: Relevance
“…Accordingly, Tamaru et al concluded that overexpression of p53 and p27KIP1 may be linked to a cellular mechanism involved in the development of the variant form of MCL [47]. Mutant p53 alleles were also correlated to proliferation signature and worse overall survival in comparison to wild-type cases [20]. In line with these observations, LOH in 17p13.1 harboring p53 were associated to members of the proliferation-associated cluster in our study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Accordingly, Tamaru et al concluded that overexpression of p53 and p27KIP1 may be linked to a cellular mechanism involved in the development of the variant form of MCL [47]. Mutant p53 alleles were also correlated to proliferation signature and worse overall survival in comparison to wild-type cases [20]. In line with these observations, LOH in 17p13.1 harboring p53 were associated to members of the proliferation-associated cluster in our study.…”
Section: Discussionsupporting
confidence: 89%
“…As previously described, we detected a high frequency of LOH in the p53 locus, which has been reported as a marker of poor prognosis associated with blastoid variants of MCL [20,21]. Accordingly, Tamaru et al concluded that overexpression of p53 and p27KIP1 may be linked to a cellular mechanism involved in the development of the variant form of MCL [47].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…1 In one of the larger reports from the Leukemia and Lymphoma Molecular Profiling Project (LLMPP), TP53 mutations were found in 16/82 (20%) of MCL samples and were associated with an unfavorable clinical course. 4 That notwithstanding, the prognostic relevance of 17p deletions (which include the TP53 gene) in MCL is less clear, although several studies have indicated an association with short survival. 5 The aim of this study was to further investigate the mutation profile and prognostic impact of TP53 mutations and 17p deletion in a large cohort of 119 MCL patients collected at university hospitals in Sweden and Finland between 1983 and 2004 (median 1999).…”
mentioning
confidence: 99%